EPISTEMOLOGI TAFSIR MULLĀ ṢADRĀ - Kerwanto Kerwanto (Jurnal Theologia, 2019)
This article aims to carry out an exploration related to the epistemological setting of Mullā Ṣadrā's interpretation. Apart from being known as the main Muslim philosopher as Ibn Sinā, Ṣadrā also describes his mystical-philosophical views in his collection of commentary treatises, Tafsīr al-Qurān al-Karīm. Through this article, the author describes a set of interpretive epistemologies used by Ṣadrā, which can be used as an epistemological offer to bridge several issues of Sufi interpretation (tafsīr al-ishārī), especially in the validity of its disclosure method. In addition to the method of interpretation, there are other unique things contained in this article, such as: mukāshafah as the main foundation of interpretation as it applies generally in the Sufi interpretation (tafsīr al-ishārī), sources of interpretation (maṣādir al-tafsīr) and the style of explanation of the commentary (uslūb al-tafsīr) that Ṣadrā uses. Furthermore, to complete this paper, the author also describes Ṣadrā's view of the ontology of the Quran as the basis of his interpretation epistemology.